2013
DOI: 10.1128/jvi.01443-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Analysis of the Novel ORF4 Protein Encoded by Porcine Circovirus Type 2

Abstract: bPorcine circovirus type 2 (PCV2) is the primary causative agent of porcine circovirus-associated diseases in pigs. To date, viral proteins Cap, Rep, Rep=, and ORF3, encoded by the PCV2 genome, have been described. Here, transcription and translation of a novel viral gene within the PCV2 genome (designated ORF4) was determined and functionally analyzed in vitro and in vivo. Northern blot analysis indicated that the RNA transcribed from the ORF4 gene is about 180 bp in length and overlaps ORF3 in the same direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
89
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 49 publications
3
89
0
Order By: Relevance
“…Among them, PCV2 ORF1 encodes a gene for virus replication, and ORF2 encodes a gene for capsid formation (Mankertz et al, 1998;Nawagitgul et al, 2000). ORF3 and ORF4 may regulate host immune responses by interacting with host proteins (Liu et al, 2005(Liu et al, , 2006(Liu et al, , 2007He et al, 2013). The function of PCV2 ORF3 may be to activate host cell signalling, whereas the function of PCV2 ORF4 may be to downregulate host cell signalling (Liu et al, 2007;He et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, PCV2 ORF1 encodes a gene for virus replication, and ORF2 encodes a gene for capsid formation (Mankertz et al, 1998;Nawagitgul et al, 2000). ORF3 and ORF4 may regulate host immune responses by interacting with host proteins (Liu et al, 2005(Liu et al, , 2006(Liu et al, , 2007He et al, 2013). The function of PCV2 ORF3 may be to activate host cell signalling, whereas the function of PCV2 ORF4 may be to downregulate host cell signalling (Liu et al, 2007;He et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…ORF3 and ORF4 may regulate host immune responses by interacting with host proteins (Liu et al, 2005(Liu et al, , 2006(Liu et al, , 2007He et al, 2013). The function of PCV2 ORF3 may be to activate host cell signalling, whereas the function of PCV2 ORF4 may be to downregulate host cell signalling (Liu et al, 2007;He et al, 2013). In particular, a previous experiment demonstrated that PCV2 infection in host cells activates NFkB by IkBa degradation (Wei et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ORF1 encodes the Rep and Rep' proteins involved in viral replication (Cheung 2003). ORF3 (Liu et al 2005(Liu et al , 2006 and ORF4 (He et al 2013) encodes non-structural (NS) proteins related to viral pathogenesis. ORF2 encodes the major structural capsid protein (Cap, 30 kDa), which is also the main antigenic determinant of the virus (Nawagitgul et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Among the four major ORFs of PCV2, ORF1, which is also termed the 'rep' gene, encodes the viral replicase and ORF2 (the 'cap' gene) encodes the capsid protein (Mankertz et al, 1998;Nawagitgul et al, 2000). ORF3 and ORF4 encode nonstructural genes that may modulate the phenotype of host cells (Liu et al, 2005(Liu et al, , 2006(Liu et al, , 2007He et al, 2013).…”
mentioning
confidence: 99%